Per- and polyfluoroalkyl substances (PFAS) in the cryosphere – occurrence, organismic accumulation, ecotoxicological impacts, transformation, and management strategies - Arulananthan, Ashani; Vilhelmsson, Oddur Þór; Karsten, Ulf; Grossart, Hans-Peter; Sigurbjörnsdóttir, Auður; Rolfsson, Óttar; Joerss, Hanna; Scholz, Bettina (Frontiers in Environmental Science, 2025)
The cryosphere faces increasing threats from anthropogenic pollutants, including per- and polyfluoroalkyl substances (PFAS), a class of synthetic chemicals produced in significant quantities and released into the environment for over seven decades. PFAS are widely utilized for their water- and grease-resistant properties in numerous industrial, household, personal care, and medical products. Despite their widespread applications, all PFAS or their degradation and transformation products are environmentally persistent and pose health risks to humans. PFAS are detected ubiquitously, even in remote regions like the Arctic and Antarctica, and they bioaccumulate within polar trophic food chains. The primary transport and transmission mechanisms for PFAS involve atmospheric transport through volatile precursors, atmospheric oxidation, ocean currents, and the formation of sea spray aerosols. Additionally, contamination of surface snow, post-deposition processes in snow, and sediment interactions significantly contribute to PFAS transport. The physical and chemical properties, including density, melting points (Tm), boiling points (Tb), solubility, vapor pressure, electronegativity, low polarizability, chemical stability, and thermal stability, play key roles in determining their environmental fate and transformation. The toxicity of certain PFAS has raised concerns, prompting bans and efforts to develop safer alternatives. Despite increasing public awareness and regulations to limit the production of legacy PFAS, their long-term environmental impacts remain unclear. As global warming accelerates cryosphere shrinkage, which releases PFAS with meltwater, cold-adapted ecosystems and associated biota face unprecedented challenges and uncertainties, particularly regarding the accumulation of non-degradable materials. This situation underscores the urgent need to comprehensively understand the fate of PFAS and adopt effective management strategies for polar systems. This review summarizes current literature on the transport, distribution, and legacy of PFAS, along with their known ecological impacts, bioremediation potential, and other management options in the cryosphere.